Surimi Quality Leaftail Croaker Fish with Differences of Leaching Frequency - Dini Surilayani; Ririn Irnawati; Rifki Prayoga Aditia (Jurnal Perikanan dan Kelautan, 2019)
Leaftail croaker fish (Johnius sp) is one of less economically important demersal bycatch, abundant yet underutilized. Efforts to increase the economic value into surimi product, since it has tender, white and thick texture of meat. As an important factor in surimi production process, this study aimed effects of different leaching frequency on chemical and physical characteristics of product in order to obtain its optimum frequency. Completely randomized design was used with 3 different leaching frequency and 3 repetitions. Further, each sample were analysed chemically using proximate analysis (water content, protein content and fat content) and physically using sensory analysis (folding and cutting test). Statistical non parametric Kruskal Wallis test was conducted to have significance level of folding and cutting test. More leaching frequency increases water content value, but decrease protein and fat content value in surimi. Statistical analysis suggested that optimum characteristics of surimi resulted from 2 times leaching with water content of 82.61%, protein content of 15.58% and fat content of 0.36%. Although, sensory analysis showed that leaching frequency positively correlated to the value of folding and cutting test, 2 times leaching was also optimum for surimi production process.